Ictiofauna de la Bahía de Navidad, Jalisco, México - Aguilar-Palomino, Bernabé (Universidad de Costa Rica, 2001)
A check-list and the relative abundance of the ichthyofauna from Bahia de Navidad, Jalisco, Mexico is presented. This poorly known area of the eastern Tropical Pacific ocean is characterized by its great fish diversity. A total of 245 fish species (163 genera, 72 families) were collected during the 1994-1995 annual cycle. Vouchers were deposited in Centro de Ecologia Costera, Universidad de Guadalajara. The most important families in number of species were Carangidae (20 species), Haemulidae (20), Serranidae (17), Sciaenidae (13) and Lutjanidae (8); 20 species represented 85 % and 80 % of relative abundance and biomass respectively. Microlepidotus brevipinnis, Caranx caninus, Caranx caballus, Kiphosus analogus and Caranx sexfasciatus, were the dominant species. Most fish species collected in Bahia de Navidad have zoogeographical affinity with the Panamic Province (65%), and in lesser proportion with the Eastern Pacific Ocean (19%), Circumtropical (7%), Mexican Province (5%), Indo-Pacific Ocean (3%) and Gulf of California (0.4%). The great ichthyological affinity between the study area and the southern Gulf of California suggests an extension of the of Gulf southern limit.